Proposing a Quality Inspection Process Model Using Advanced Technologies for the Transition to Smart Building Construction - Shin, Hyeon Ju; Cha, Hee Sung (Sustainability (Switzerland), 2023)
With advancements in new technologies in the industry, efforts have been made to adopt various smart devices during the life cycle of building construction. However, little attention has been paid to developing a work process model to maximize the benefits of smart technologies. While identifying the shortcomings of conventional quality inspection, this study configures a new quality inspection process model in collaboration with smart devices. Based on the proposal, the study developed a new tool that effectively improves the current quality inspection practice. The final goal of this research is to propose a novel inspection process model by developing an Application Programming Interface (API) system using Building Information Model (BIM) software. Additionally, to verify the applicability of the system, this study includes a case study on tile work and confirms the effects of a prototype of the proposed system through an expert survey. The survey results reveal that the proposed system is effective and practical. This research contributes to maximizing the effectiveness of using smart devices and supporting effective application in smart construction.
Keywords: application programming interface (API); building information modeling (BIM); construction quality inspection; smart building construction; smart technologies